PREVALENCE OF PULMONARY TUBERCULOSIS AMONG CHILDREN LIVING IN SAMARU, ZARIA, NIGERIA: A CASE STUDY OF â€˜AL MAJIRIâ€™ CHILDREN - Mubarak, M.; Atta, H. I.; Salihu, M. K. (FUDMA Journal of Sciences, 2020)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, and it is still a major health problem in Nigeria especially among people with poor socio-economic status. This study was conducted with the aim of determining the prevalence of tuberculosis among two study subjects living in Hayin Dogo community of Samaru, Zaria, Kaduna state: â€œAl majiraiâ€ (Qurâ€™anic school children) and children showing respiratory symptoms The major focus of this study is the al majirai, due to their unhygienic, overcrowded living environments and poor nutritional status. Two hundred sputum samples were collected from the al-majirai, and one hundred from the other children; convenience sampling method was employed. The samples were stained using the Ziehl Neelsen technique and observed microscopically for the presence of acid fast bacilli. The prevalence of acid fast bacilli (AFB) among the Al majirai was 0%, and 12% among the children attending the medical center. Symptoms such as night sweat and bloody sputum, as well as risk factors such as malnutrition and poor housing hygiene were found to be significantly associated with the infection in the children showing respiratory symptoms and attending the Ahmadu Bello University medical center (P
Keywords: Acid fast bacilli; Samaru; al-majirai; children, tuberculosis